A new species of Miccolamia Bates, 1884 (Coleoptera: Cerambycidae: Lamiinae) from northeast India, with comments on related species - Sreedevi, Kolla; Agossadou, Anette Houefa; Kumar, Umesh; Ghate, Hemant V. (Zootaxa, 2020)
A new species of Cerambycidae, Miccolamia (Miccolamia) arunachalensis Sreedevi & Ghate sp. nov. (Lamiinae: Desmiphorini) is described from northeast India. This is the fourth species of Miccolamia from India. Additionally, an updated key to the Indian species is also provided along with comments on related species of the subgenus.